Zinc fertilization effects on agromorphological and quality parameters of commonly grown rice (SAARC Journal of Agriculture, 2014)
Among the micronutrients, zinc deficiency is widespread throughout the world particularly in low land rice fields causing low yields and affecting nutritional quality of the produce. In present investigation, 26 rice cultivars including some locals, aromatics, HYVs and hybrids grown on an Inceptisols with no Zn, basal Zn and soil+foliar applied Zn were evaluated for agro-morphological and quality parameters in a strip plot design having three replications during kharif season for consecutive two years (2009 and 2010). Rice cultivars differed significantly in their native agro-morphological parameters as well as among cultivar categories. Grain and straw yield as well as harvest index of different cultivars showed wide variations both with and without Zn application. On average, grain yields of different rice cultivars increased by 29% and 22% with soil plus foliar and only soil application of Zn, respectively. Regarding yield efficiency, HYV showed highest efficiency followed by hybrid, aromatic and local cultivars, irrespective of Zn fertilization. Applications of Zn, both as basal and as soil+foliar application significantly reduced the Fe content in brown rice irrespective of the cultivar grown. DOI: http://dx.doi.org/10.3329/sja.v11i1.18388 SAARC J. Agri., 11(1): 105-120 (2013)